Characterizing the transition from paediatric to adult care among emerging adults with Type 1 diabetes. Issue 5 (28th February 2013) - Helgeson, V. S.; Reynolds, K. A.; Snyder, P. R.; Palladino, D. K.; Becker, D. J.; Siminerio, L.; Escobar, O.
Abstract Aims The goals of the study were to describe the transition of youth with Type 1 diabetes from paediatric to adult healthcare services, examine the link of this transition with self care and glycaemic control, and distinguish youth who received medical treatment from different physicians in terms of demographic and parent relationship variables. Methods Youth with Type 1 diabetes (n = 118) were enrolled in a prospective study that examined the transition from the paediatric to adult healthcare systems and were evaluated during their senior year of high school (time 1) and 1 year later (time 2). Data on self care, glycaemic control and parent relationship were collected. Results The majority of youth saw a paediatric endocrinologist at both assessments (n = 64); others saw an adult care physician at both assessments (n = 26) or transitioned from a paediatric endocrinologist to an adult care physician (n = 19). Nine youth saw no physician between time 1 and time 2. There were group differences in demographic and parent relationship variables and self‐care behaviour and glycaemic control related to the transition of care. Youth who remained in the paediatric healthcare system had the best self care and did not experience declines in glycaemic control over time. Conclusions Early transition from the paediatric healthcare system to the adult healthcare system is associated with psychosocial variables and worse glycaemic control. Future research should identify factors that determine optimal timing and strategies to avoid deterioration of care and control during this transition.